Revisiting the link between consumer sentiment and economic activity: Consumer confidence and economic growth - (:unkn) unknown (IGI Global, 2015)
This chapter revisits the relationship between consumer confidence(sentiment) and economic and financial variables for the emerging market of Turkey using the recently developed and superior frequency domain causality and wavelet comovement analysis. The main theme is to assess the information content and the relationship of consumer confidence indices (which are advocated to be leading economic indicators) with important economic and financial variables in Turkey. This will help to understand the dynamics of interaction between households, firms and the public sector in Turkey. There are two basic contributions of this study to the existing literature: first, as far as we know, this study is the first of its' kind concentrating on the consumer confidence and several other financial parameters for an emerging market by adopting a frequency domain and wavelet comovement analyses. Second, the use of frequency analysis enables us to examine the test results over different frequencies rather than limiting ourselves in time domain and a linear world. © 2016 by IGI Global. All rights reserved.